La répartition des établissements industriels à Sfax : un schéma radio-concentrique - Monia Gasmi (Revue des Mondes Musulmans et de la Méditerranée)
While the spatial organization of metropolitan industry in developed countries has been widely studied, cities in developing countries engaged in a process of industrialization, have not, to the best of our knowledge, benefited from similar, quantitative geographical studies. Making use of techniques infrequently applied in the study of developing economies, we have attempted to analyse the geographical distribution of industrial establishments in Sfax, Tunisia. The study reveals the existence of an archaic radioconcentric model in use among northern countries prior to the 1950's. The study of industrial space allocation, the main topic of our article and a classical problem of economic geography, makes it possible to close the gaps in the literature of Tunisian industrial geography. It provides essential visual and analytical support for decisions of geographical import, whether for company management, urban planners or developers.